The pests of crops in Indonesia - Kalshoven, Louis George Edmund (Ichtiar Baru, 1981)
This books focuses on the pests (mainly arthropod) of economic plants and plant products and their natural enemies in Indonesia. This edition has been expanded to include some of the large amount of additional relevant material that has accumulated over the past 30 years. Because of the need for frequent revision, details of chemical control measures are not given; there is increasing emphasis on integrated control, and for many of the pests notes are given on natural enemies and their use as biological control agents